(untitled) (Modern education and development, 2025)
This article explores the critical role of phonetics in English language education, emphasizing its importance for both learners and teachers. It delves into various aspects of phonetics instruction, including the identification of key sounds, the application of articulatory phonetics, and the integration of practical exercises and technological tools. The paper also discusses the challenges educators face in teaching phonetics and provides practical strategies to overcome these obstacles. By examining the necessity of clear pronunciation for effective communication, this article advocates for the development of a comprehensive phonetics-focused approach in English language teaching to enhance learner outcomes.